Ramadhan Momentum Transformasi Dakwah Digital Sebagai Upaya Membangun Kedigdayaan Islam - Haq, Ihsan Abdul (Ikatan Da'i Indonesia, 2024)
Digital transformation has affected various aspects of human life, including da'wah in the Islamic context. This article explores the impact and implications of the digitalization transformation in da'wah practice from the conventional way of da'wah that is limited in reach and thus lacks audience engagement, to through the use of information and communication technology, da'wah becomes more accessible, disseminated, and understood by the wider community. Digital approaches also allow for new opportunities to interact with audiences globally and expand the reach of religious messages. However, along with these opportunities, some challenges need to be addressed, such as content accuracy, data security, and the diversity of religious interpretations. This article is written using the Literature Study method, which hopes to produce scientific research related to Digital Da'wah. So that with a deep understanding of this, digital da'wah can be an effective tool for Islamic Empowered to strengthen religious communication, promote tolerance, and build cross-cultural understanding within today's global diversity framework. An emphasis on collaboration, quality research, and a sustainable visionary direction is needed to optimize the transformative potential of digitalization in future da'wah activities.